ANALISIS PENGARUH FINANCING TO DEPOSIT RATIO (FDR) TERHADAP PROFITABILITAS PERBANKAN SYARIAH DI INDONESIA - Suryani Suryani (LP2M - Universitas Islam Negeri (UIN) Walisongo, 2011)
This study aimed to (1) analyze the condition of Financing to Deposit Ratio (FDR) of Islamic Banking in Indonesia, (2) analyze the profitability of sharia banking in Indonesia; and (3) to analyze the influence of Financing to Deposit Ratio (FDR) of the profitability of sharia banking in Indonesia. This study took samples at Islamic banks in Indonesia including 11 Islamic Banks (BUS), 23 Business Units of Sharia Banking (UUS). The research data is from Islamic Banking Statistics published by Bank Indonesia from January 2008 until December 2010 (Financial Ratio Study to BUS and UUS period 2008-2010). The number of Islamic banks used is 34 banks. The technique uses simple linear regression analysis with the help of the program EVIEWS version 5.